Necrotic and apoptotic volume changes of red blood cells investigated by low-angle light scattering technique. Issue 2 (2007) - Mindukshev Mindukshev, Igor V. Igor V.; Krivoshlyk Krivoshlyk, Vladimir V. Vladimir V.; Ermolaeva Ermolaeva, Elena E. Elena E.; Dobrylko Dobrylko, Irina A. Irina A.; Senchenkov Senchenkov, Evgeniy V. Evgeniy V.; Goncharov Goncharov, Nikolay V. Nikolay V.; Jenkins Jenkins, Richard O. Richard O.; Krivchenko Krivchenko, Alexander I. Alexander I.
Abstract : A low-angle light scattering technique, which has been applied previously to studies of blood platelets and Ehrlich ascite tumor cells, revealed differences in the dynamics of necrotic and apoptotic red blood cell death. Under hypotonic loading or in ammonia medium, red blood cells (RBC) swelled to a critical size (diameter approximately 13 μ m) prior to hemolysis (necrosis). Under acidic loading, hemolysis occurred with less pronounced swelling of cells (diameter approximately 10 μ m). Apoptosis induced by a calcium ionophore resulted in initial formation of echinocytes, followed by development of rounded red blood cells with uneven membrane, capable of agglomeration. In such a way, RBC aggregation can precede the final stages of the RBC apoptosis when small cellular fragments are generated. On the basis of erythrograms of the cells hemolysing in ammonia medium, the echinocytic (preapoptotic) and stomatocytic (prenecrotic) RBC were discerned due to the very high resistance of apoptotic RBC to osmotic (ammonia) loading.